Morphology of Glenoid Cartilage Defects in Anteroinferior Glenohumeral Instability. Issue 4 (4th April 2022) - Kawakami, Jun; Yamamoto, Nobuyuki; Itoi, Eiji; Henninger, Heath; Tashjian, Robert; Chalmers, Peter N.
Background: Glenoid cartilage defects may contribute to anterior shoulder instability recurrence and progression to osteoarthritis, but their morphology remains unknown. Purpose/Hypothesis: The purpose was to determine the shape, size, and location of glenoid cartilage defects and the prevalence and risk factors for cartilage defects in the setting of anterior glenohumeral instability. It was hypothesized that glenoid cartilage defects would be common, would be associated with recurrence of dislocation, and would share similar morphology with glenoid osseous defects. Study Design: Cross-sectional study; Level of evidence, 3. Methods: In this retrospective study, all patients who underwent arthroscopic surgical treatment for anterior glenohumeral instability between January 2012 and May 2019 were included; excluded were patients with documented posterior or multidirectional instability or previous glenohumeral surgery. For each patient, the operative report, arthroscopic images, and preoperative magnetic resonance imaging (MRI) scans were reviewed to determine the prevalence of cartilage injury. For those patients with an Outerbridge grade 3 or 4 defect, the cartilage surfaces on the MRI scans were segmented to make 3-dimensional (3-D) segmentations. From these 3-D segmentations, we measured length, width, and surface area of the glenoid and defect, and the orientation of the defect relative to the superior and inferior poles of the glenoid. A multivariable analysis was conducted to determine correlates with cartilage damage. Results: In 322 patients treated operatively for anterior glenohumeral instability, 38% had a concomitant cartilage defect. The mean cartilage defect was located directly anteriorly at the 3:07 clockface position (range, 2:10-4:05) and encompassed 6.5% ± 3.5% of the glenoid surface area. However, defects ranged up to >56% of glenoid length and up to 27% of glenoid width, and the largest defect encompassed 19.5% of the glenoid cartilage surface area. Patients with a cartilage defect were more likely to be male ( P = .031) and to have undergone a concomitant posterior labral repair ( P = .018). Conclusion: Cartilage defects were common in patients with operatively treated anterior glenohumeral instability, occurring in 38% of patients. These defects were located directly anteriorly at 3:07, similar to osseous glenoid defects. Future prospective studies with cartilage-specific MRI sequences should be conducted.